Regulation of the HBV Entry Receptor NTCP and its Potential in Hepatitis B Treatment - Li, Yan; Zhou, Jun; Li, Tianliang (Frontiers in Molecular Biosciences, 2022)
Hepatitis B virus (HBV) is a globally prevalent human DNA virus responsible for more than 250 million cases of chronic liver infection, a condition that can lead to liver inflammation, cirrhosis, and hepatocellular carcinoma. Sodium taurocholate co-transporting polypeptide (NTCP), a transmembrane protein highly expressed in human hepatocytes and a mediator of bile acid transport, has been identified as the receptor responsible for the cellular entry of both HBV and its satellite, hepatitis delta virus (HDV). This has led to significant advances in our understanding of the HBV life cycle, especially the early steps of infection. HepG2-NTCP cells and human NTCP-expressing transgenic mice have been employed as the primary cell culture and animal models, respectively, for the study of HBV, and represent valuable approaches for investigating its basic biology and developing treatments for infection. However, the mechanisms involved in the regulation of NTCP transcription, translation, post-translational modification, and transport are still largely elusive. Improvements in our understanding of NTCP biology would likely facilitate the design of new therapeutic drugs for the prevention of the de novo infection of naïve hepatocytes. In this review, we provide critical findings regarding NTCP biology and discuss important questions that remain unanswered.